Supporting democracy when other democracies prosper? - Wang, Yi-Ting (Democratization, 2023)
Public support has long been considered crucial for the vitality and survival of democracy. Although the determinants of citizens' support for democracy have been extensively studied, current literature puts emphasis on domestic factors. While another body of scholarship has documented the propensity of political diffusion, most studies focus on aggregate outcomes, and citizens' attitudes within this tendency have received less attention. Extending the research on the influence of domestic performance on public attitudes and verifying the micro-foundation underlying political diffusion, we argue that economic performance of other countries can similarly shape citizens' support for democracy. Using a sample of more than 90 democratic countries across the globe over the past three decades, we find that citizens in democratic countries are more likely to view democracy as the ideal regime type when there is a positive correlation between the level of democracy and economic growth across proximate countries, either geographically or culturally defined. We also show that the effects of proximate foreign democracies' economic performance in boosting democratic support are particularly evident in countries where citizens have greater access to external information, as they are more aware of the political systems and economic conditions of foreign countries.